Two new and threatened Eugenia (Myrtaceae) species from the Atlantic Forest of Espírito Santo, Brazil - Valdemarin, Karinne Sampaio; Souza, Vinicius Castro; Mazine, Fiorella F. (Phytotaxa, 2020)
During our studies on Eugenia of Espírito Santo state, Brazil, two new species came out of our attention being here described, illustrated and compared morphologically with their similar species. Eugenia mestrealvarensis can be easily recognised by its clusters of fascicules on trunk with pedicellate flowers, an unusual feature among the species of the genus, and E. penduliflora by its two-flowered raceme with later vegetative proliferation with pendular pedicels. Both species are evaluated as critically endangered following IUCN red list criteria, being E. mestrealvarensis restricted to the Área de Proteção Ambiental Estadual de Mestre Álvaro, and E. penduliflora to the Reserva Natural Vale, in Espírito Santo state.